Structural study of Ni-substituted YBaCo4-xNixO7 frustrated cobaltites - Torre, Luis Maria (2015)
In this work we report a study of the thermal stability and the evolution of the crystal structure of Ni-substituted YBaCo4-xNixO7 cobaltites, for x=0, 0.10 and 0.20. Synchrotron X-ray powder diffraction and thermodiffraction experiments show that the structural transition P31c→Pbn21, which occurs around room temperature for the parent compound, is shifted up to 40 by the partial substitution Ni-for-Co. Moreover, the transition is shown to be of first order with a volume collapse of ≈0.05% and an abrupt contraction of the cell along the c-direction. The monoclinic distortion below 100 K reported for the parent compound is also observed in the Ni-substituted samples, suggesting that they also get to order antiferromagnetically below that temperature. Magnetization measurements allowed us to detect a small amount of a ferromagnetic impurity in the sample with x=0.20, indicating that the solubility limit of Ni lies below that value. The magnetic susceptibility in the paramagnetic region, as well as the cell parameters in each crystallographic phase, is not significantly modified by these amounts of Ni substitution, in contrast to the marked enhancement of the P31c phase stability upon substitution.